Motels in Serbia – what do potential guests expect? - Pavić, Lazar; Blešić, Ivana; Nerandžić, Branislav; Vukosav, Svetlana; Mumel, Damijan (Industrija, 2018)
The main aim of the paper is to investigate potential guests’ expectations in Serbian motels. Through the literature review process, it was determined that there is a cack of research about motel guests’ expectations. Based on the survey research on 237 potential motels’ guests 14 dimensions of guests’ expectations were determined. Statistical significant differences in guests’ expectations dimensions among sociodemographic profile were also investigated (Gender, Age, Monthly Income, Occupational Status, Marital Status, Growing up Place, Reason for Traveling, Country of Origin). In Conclusions are present proposal for future motel products development based on presented results as also future research proposals.